Editorial: The reciprocal relationship between sleep and stress in elite athletes - Vitale, J. A.; Nedelec, M.; Skorski, S.; Lastella, M. (Frontiers in Psychology, 2021)
Modern elite athletes are facing more mental, emotional and social demands than ever before, including, amongst others, pressure on personal relationships, media demands, sponsor needs and public interest (Walsh et al., 2021). The majority of elite athletes sleep less than the recommended night-time sleep duration of 7-9 h per night and obtain less than their self-assessed sleep need (Sargent et al., 2021). Many endogenous and environmental factors are able to negatively influence sleep duration and quality in athletes, including evening high-intensity training, pre-competition anxiety, mental fatigue or long-haul travel (Aloulou et al., 2021; Janse van Rensburg et al., 2021; Walsh et al., 2021). Unfortunately, poor sleep can have negative effects on both psychological and physiological aspects which can ultimately lead to an impairment of physical and mental performance (Fullagar et al., 2015; Filipas et al., 2021; Vitale et al., 2021). Thus, it was the aim of this Research Topic to explore the reciprocal relationship between sleep and stress, and to provide insights into potential contributions regarding athletic performance and health.